Investigating Automobile Passengers’ Comfort and Safety on Scenic Road Using Sideway Force Coefficient - Ronghua Wang; Xingliang Liu; Feijie Han (Advances in Materials Science and Engineering)
To satisfy passengers’ experiential demand in scenic roads, a study on passengers’ comfort in the aspect of horizontal curve design is stated in this study. A new indicator sideway force coefficient (SFC) describing passengers’ comfort is introduced, which differs from lateral acceleration. The mechanism of SFC is provided depending on the dynamic balance condition of the vehicle on horizontal curve and SFCc representing passengers’ comfort tolerance limitation is investigated. A large scale naturalistic driving experiments along a park road are conducted, and the SFCc value from naturalistic driving experiments is verified through numerical simulation of 15 horizontal curves from 5 scenic roads from the perspectives of both passengers’ comfort and driving safety. The statistical analysis on data collected in field tests indicates that age and gender have no effect on SFCc, and the value of SFCc is determined as 0.291. The corresponding minimum radius limits under 20–60 km/h and superelevation 6%, 8%, and 10% are proposed. The numerical simulation denotes, when satisfying the comfort demand of passengers (SFC less than 0.291), the lateral distance path is in a safe range, which could also satisfy the safe driving requirements. Thus, SFCc and minimum radius limits proposed in this study are proved to be credible and appropriate for the curve design of horizontal alignment in scenic roads.